The perfective aspect in english and portuguese: a constrative study on semantic basis - Monteiro, Dirce Charara; Neves, Maria Helena de Moura; Rodrigues, Sonia Veasey (ALFA: Revista de Linguística, 2001)
An exam of the occurrences of the PRESENT PERFECT in Englishwas made in such a way as to establish the prevailing semantic features ofthis verbal form. I t was verified up to what an extent the meaning of thePERFECTIVE thus characterized is expressed in the corresponding Portuguesesentences in the PRETÉRITO PERFEITO. It was found that in Portuguesethe verbal inflexion itself characterizes in a much smaller degree the PERFECTIVE ASPECT.